2008
DOI: 10.1016/j.bbabio.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of elimination of malfunctioning mitochondria (mitoptosis): Formation of mitoptotic bodies and extrusion of mitochondrial material from the cell

Abstract: Energy catastrophe, when mitochondria hydrolyze glycolytic ATP instead of producing respiratory ATP, has been modeled. In highly glycolyzing HeLa cells, 30-50% of the population survived after inhibition of respiration and uncoupling of oxidative phosphorylation for 2-4 days. The survival was accompanied by selective elimination of mitochondria. This type of mitoptosis includes (i) fission of mitochondrial filaments, (ii) clustering of the resulting roundish mitochondria in the perinuclear area, (iii) occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 44 publications
5
85
0
Order By: Relevance
“…A very recent study has shown that ROS might be involved in mitochondrial extrusion (21). As we previously reported (13), TNF␣ induced robust ROS accumulation in c-Flip Ϫ/Ϫ MEFs (Fig.…”
Section: The Caspase-dependent Pathway Plays a Crucial Role In Mitochsupporting
confidence: 62%
“…A very recent study has shown that ROS might be involved in mitochondrial extrusion (21). As we previously reported (13), TNF␣ induced robust ROS accumulation in c-Flip Ϫ/Ϫ MEFs (Fig.…”
Section: The Caspase-dependent Pathway Plays a Crucial Role In Mitochsupporting
confidence: 62%
“…Such observations are further supported by studies using mitochondrial respiratory chain uncouplers and mitochondrial poisons in which overproduction of ROS could be observed without reductions in cellular ATP levels leading to mitoptosis (20). The specific removal of dysfunctional or ROS-overproducing mitochondria during apoptosis or mitoptosis is believed to be achieved by autophagy either by autophagosome formation (mitophagy) or by the formation of mitoptot- ic bodies that are subsequently released into the extracellular environment (19). The elimination of dysfunctional mitochondria is further supported by studies of cells treated with staurosporin, a common drug used to induce apoptosis, and by the use of pan-caspase inhibitors in which cells survive but lose their mitochondria (21).…”
supporting
confidence: 50%
“…Induction of mitoptosis and concomitant disruption of ATP supply by mitochondria are often followed by activation of autophagy to assure maintenance of energy supply (Fig. 3, left panels) (Jangamreddy and Los 2012;Mijaljica et al 2010 2012)], or the mitoptotic bodies may be extruded from the cell (Lyamzaev et al 2008). During the ''outer mitochondrial membrane mitoptosis'', the mitochondria undergo condensation, followed by swelling and fragmenting of cristae, and finally the outer mitochondrial membrane bursts with vesicular remnants of cristae floating in the cytoplasm.…”
Section: Mitoptosismentioning
confidence: 99%